2018
DOI: 10.1002/cncr.31353
|View full text |Cite
|
Sign up to set email alerts
|

HOTAIR gene polymorphisms contribute to increased neuroblastoma susceptibility in Chinese children

Abstract: The results of the current study verified that HOTAIR gene polymorphisms are associated with increased neuroblastoma risk and suggest that HOTAIR gene polymorphisms might be a potential biomarker for neuroblastoma susceptibility. Cancer 2018;124:2599-606. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 67 publications
(173 reference statements)
0
26
0
Order By: Relevance
“…In addition, a total of 469 NB cases and 998 healthy controls were also included in this study [43]. Of those, 275 NB cases and 531 controls were from Guangzhou Women and Children’s Medical Center [4446], 118 cases and 281 controls were from The First Affiliated Hospital of Zhengzhou University [4749], and 76 NB cases and 186 controls were from the Second Affiliated Hospital of Xi'an Jiaotong University (Supplementary Table 2). The cases were patients diagnosed with NB, and the controls were recruited from the same hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a total of 469 NB cases and 998 healthy controls were also included in this study [43]. Of those, 275 NB cases and 531 controls were from Guangzhou Women and Children’s Medical Center [4446], 118 cases and 281 controls were from The First Affiliated Hospital of Zhengzhou University [4749], and 76 NB cases and 186 controls were from the Second Affiliated Hospital of Xi'an Jiaotong University (Supplementary Table 2). The cases were patients diagnosed with NB, and the controls were recruited from the same hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the correlation between neuroblastoma susceptibility and HOTAIR has been reported in Chinese children. By association analysis and further stratification, three HOTAIR SNPs, rs12826786, rs874945 and rs1899663, were identified as being associated with increased neuroblastoma risk, predominantly in females and among patients with a tumor in the retroperitoneal region or mediastinum [42]. Also, in a Chinese case–control study, the association of the GWAS-identified lncRNA LINC00673 rs11655237 polymorphism with neuroblastoma susceptibility was assessed, confirming that this allele significantly increased the risk of tumor, particularly in cancer originating from the adrenal gland and clinical stage IV neuroblastoma [43].…”
Section: Methods For Detection Of Snps and Measurement Of Associatmentioning
confidence: 99%
“…The characteristics of participants were described in our previous studies ( Supplementary Table 1 ) [ 33 36 ]. The genotype frequencies of the four XRCC1 polymorphisms (rs1799782 G>A, rs25487 C>T, rs25489 C>T and rs915927 T>C) in the neuroblastoma cases and controls are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Details of the selection criteria and characteristics of the study participants were provided elsewhere [ 33 36 ]. In brief, 393 neuroblastoma cases and 812 healthy controls were included in this study.…”
Section: Methodsmentioning
confidence: 99%